Developing Blockchain Algorithms in the IoT Network to Secure DataIntegrity and System Scalability - Jamil, Layla Safwat (Iraqi Journal of Science, 2024)
The Internet of Things and the blockchain are considered to be the major technologies that are linked together to support the flexibility, scalability, and integrity of the system. IoT devices have insufficient computing capacity in terms of processing data units and storage requirements. It requires efficient encryption algorithms. Nowadays, the IoT is facing several challenges, such as poorinteroperability, security vulnerabilities, privacy, and a lack of industry standards. In this paper, a novel triple DES-based blockchain algorithm for the IoT network environment is designed to assure data integrity and system scalability. Initially, the IoT network modeling is framed with different network entities, smart devices, and communication devices. Based on the received requests, the required data are processed via the Triple DES technique. The IoT requests are processed and then authenticated using a blockchain interface. If it is verified, then the service is instantiated; otherwise, it is rejected. This blockchain interface performs similarly tothe security gateway for web communication services. It prevents unauthorized third-party networks. The security layer is framed using Triple DES, which takes the least computational effort over the requested data. Here, the blockchain interface acts as an additional security layer that imbues all devices. It is clearly understood from the results that the proposed technique, blockchain-based Triple DES, outperforms the RSA algorithm in terms of computational time.